Algorithmic Governance, Market Inequality, and MSME Resilience in Indonesia’s Digital Platform Economy: A Qualitative Study - Mohammad Nurul Ulin Nuha; Dana Azizah Rahmat; Muhammad Fajar Wahyudi Rahman (Yayasan Darussalam Bengkulu, 2026)
Background: Indonesia’s digital platform economy has expanded market access for micro, small, and medium enterprises (MSMEs), yet prior studies have not sufficiently examined how algorithmic opacity interacts with capital constraints to produce differential visibility outcomes for MSMEs. Purpose: This study explores how algorithmic governance shapes MSME fragility and resilience in Indonesia’s digital platform economy by examining visibility dependence, unequal platform literacy, capital-based exposure, and collaborative adaptation. Method: Using a qualitative exploratory case-study design, this study draws on semi-structured interviews with MSME owners/managers operating on major Indonesian e-commerce platforms. The data were analyzed through iterative thematic coding, constant comparison, and source triangulation across participant accounts and supporting contextual documents. Results: The findings reveal five major themes: algorithmic opacity as a source of visibility fragility, cognitive stratification in MSME adaptation, capital fragility and unequal platform exposure, collaboration as collective resilience, and the need for fair platform governance and inclusive digital policy. These findings indicate that MSME resilience is not determined merely by access to digital platforms, but by sellers’ capacity to interpret algorithmic signals, mobilize resources, participate in collaborative networks, and operate within transparent and accountable platform ecosystems. Conclusion: The study shows that MSME resilience is shaped not only by digital adoption but also by sellers’ capacity to interpret algorithmic signals, mobilize resources, and participate in collaborative networks. This study contributes by positioning cognitive stratification as an analytical lens explaining how unequal platform literacy mediates algorithmic governance and MSME vulnerability.